Assessment and diagnosis of Developmental Language Disorder: The experiences of speech and language therapists. (May 2019) - Thomas, Sheila; Schulz, Joerg; Ryder, Nuala
Background: For many years research and practice have noted the impact of the heterogeneous nature of Developmental Language Disorder (also known as language impairment or specific language impairment) on diagnosis and assessment. Recent research suggests the disorder is not restricted to the language domain and against this background, the challenge for the practitioner is to provide accurate assessment and effective therapy. The speech and language therapist aims to support the child and their carers to achieve the best outcomes. However, little is known about the experiences of the speech and language therapist in the assessment process, in contrast to other childhood disorders, yet their expertise is central in the assessment and diagnosis of children with language disorder. Aims: This study aimed to gain an in-depth understanding of the experiences of speech and language therapists involved in the assessment and diagnosis of children with Developmental Language Disorder including the linguistic and non-linguistic aspects of the disorder. Methods and procedures: The qualitative study included three focus groups to provide a credible and rich description of the experiences of speech and language therapists involved in the assessment of Developmental Language Disorder. The speech and language therapists who participated in the study were recruited from different types of institution in three NHS trusts across the UK and all were directly involved in the assessment and diagnosis procedures. The lengths of speech and language therapist experience ranged from 2 years to 38 years. The data were analysed using inductive thematic analysis within a phenomenological approach. Outcomes and results: The analysis of the data showed three main themes relating to the speech and language therapists' experience in assessment and diagnosis of Developmental Language Disorder. These themes were the participants' experiences of the barriers to early referral (subthemes – parents' misunderstanding and misconceptions of Developmental Language Disorder, bilingualism can mask Developmental Language Disorder and public lack of knowledge of support services), factors in assessment (subthemes – individual nature of impairments, choosing appropriate assessments, key indicators and identifying non-language difficulties) and the concerns over continued future support (subthemes – disadvantages with academic curriculum, disadvantages for employment, impact of Developmental Language Disorder on general life chances). Conclusions and implications: This study provides first-hand evidence from speech and language therapists in the assessment of children with Developmental Language Disorder, drawing together experiences from speech and language therapists from different regions. The implications are that support for early referral and improved assessment tools are needed together with greater public awareness of Developmental Language Disorder. The implications are discussed in relation to the provision of early and effective assessment and the use of current research in these procedures.